The Use of Bhuppa' Bhabbhu Ghuru Rato Philosophy to Strengthen the Performance Accountability of Government Institutions - Widaninggar, Nanda; Ganis Sukoharsono, Eko; Purwanti, Lilik; Widya Prihatiningtias, Yeney (KnE Social Sciences, 2023)
This study aimed to reveal the wisdom of the State Civil Apparatus (SCA) in charge of the Government Agency Performance Accountability System (GAPAS) organization in the Situbondo Regency, Indonesia. The research focused on individual accountability practices to strengthen the performance accountability of governmental institutions based on the Madura philosophy of Bhuppa’ Bhabbhu Ghuru Rato. Ethnomethodology was conducted using four steps: indexicality analysis, reflexivity, contextual action, and common-sense presentation. The individuals involved in the GAPAS were not entirely Madurese; nevertheless, the Madura philosophy of Bhuppa’ Bhabbhu Ghuru Rato had been internalized by everyone. It was found that this philosophical understanding was not only for individuals but also could be a role model for subordinates. This philosophy was believed to be one of the success factors in achieving the A rank for three consecutive years in the GAPAS. Regional leaders need to consider the strength of the philosophy of local wisdom and internalize it in organizational management since it can positively impact individual performance. Keywords: performance, accountability, Madura philosophy, obedient, role model